El community manager, una necesidad para la correcta gestión de las marcas - Morales Salazar, Eduardo Enrique (2020)
This case study consists of the importance of Community Manager for the correct management of brands and companies. Taking charge of the marketing of the corporation is not an easy task, since the Community Manager is the one who is in charge of carrying out all these activities through the technological tools that humanity is currently developing, it is therefore, through the use of social networks, blogs, web, and all types of digital communication media that the Community Manager carries out its activities, allowing the productivity of companies to take possession of the market, offering their products of goods or services, and for the company to have direct contact and It could be said that even personalized with its customers, to solve concerns, problems and satisfy users, allowing companies and brands to establish high levels of acceptance. The Community Manager will contribute beneficially to each of the Canton's businesses, and therefore will increase commercial and labor productivity in the area. The research will contribute to the productive community, since a socialization to the commercial sector will be implemented, to publicize the importance of Community Manager in the productive sector.